2017
DOI: 10.1007/s10995-016-2243-2
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Oxidative Stress in Human Milk do not Differ by Maternal BMI But are Related to Infant Growth Trajectories

Abstract: Objective Obesity in adults is associated with inflammation and oxidative stress. Whether or not this phenotype is reflected in human milk (HM) composition, or may impact infant growth remains unknown. We investigated whether HM from overweight/obese (OW/Ob) mothers exhibited higher concentrations of inflammatory cytokines and markers of oxidative stress. We also correlated these bioactive components with infant growth patterns. Methods This was an observational cohort of 56 breastfeeding mothers and their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 36 publications
0
32
0
2
Order By: Relevance
“…Women with pre-existing conditions known to influence HM macronutrient composition, including GDM and diabetes, were excluded in most of the studies (n = 18) [23,24,26,28,29,31,[34][35][36]39,40,42,43,[45][46][47][48]50]. Two studies included women with GDM [30,32], while whether or not women with these conditions were included was unclear [27,49] or not stated [8,9,16,25,33,37,38,41,44] in 11 studies.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Women with pre-existing conditions known to influence HM macronutrient composition, including GDM and diabetes, were excluded in most of the studies (n = 18) [23,24,26,28,29,31,[34][35][36]39,40,42,43,[45][46][47][48]50]. Two studies included women with GDM [30,32], while whether or not women with these conditions were included was unclear [27,49] or not stated [8,9,16,25,33,37,38,41,44] in 11 studies.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Maternal obesity has not been observed to influence milk composition. However, it has been suggested that obese mothers can transfer via breast milk inflammatory cytokines and markers of oxidative stress, which can contribute to weight gain in the infant (Young et al., ). Although it has been shown that the profile of some fatty acids in the breast milk from obese women is different compared to lean women, their total fat, protein and carbohydrate content does not differ (Panagos et al., ).…”
Section: Pre‐ and Postnatal Events Involved In Intestinal Barrier Matmentioning
confidence: 99%
“…7 It is known today that the use of breast milk in infant feeding can reduce the risk of obesity, even if it is produced by obese mothers. 10 Studies concerning OS are correlated with the imbalance between reactive oxygen species (ROSs) and reactive nitrogen species (NREs) and with the efficiency of the antioxidant defense system. Breastfed children have been shown to have a more efficient antioxidant barrier when compared to formula-fed children.…”
Section: Introductionmentioning
confidence: 99%